Antibiotic treatment recommendations for acute respiratory tract infections in Scandinavian general practices-time for harmonization? - Malene Plejdrup Hansen; Sigurd Høye; Katarina Hedin (Taylor & Francis Group, 2024)
Introduction During recent years, the world-including Scandinavia-has experienced significant challenges with shortages of antibiotics. In Scandinavia, phenoxymethylpenicillin is recommended as first-line antibiotic treatment for most acute respiratory tract infections (ARTIs). However, the Scandinavian countries each constitute rather small markets for phenoxymethylpenicillin. The aim of this discussion paper is to enlighten the differences in Scandinavian ARTI antibiotic treatment recommendations. This information is fundamental for exploring the potential of harmonizing treatment recommendations in Denmark, Norway and Sweden-to help ensure sufficient future supply of phenoxymethylpenicillin.Methods Information from national ARTI antibiotic treatment recommendations from respectively Denmark, Norway and Sweden has been collated.Results Several discrepancies exist in recommendations. Adult dosage varies from a minimum of 660 mg x 4 (Denmark) to a maximum of 2000 mg × 3 (Sweden). Within Norway and Sweden, variations in recommended dosage also exist between the different types of ARTIs. A main challenge is that the tablet strengths recommended, and available on the market in the three countries, differs.Also, antibiotic treatment durations vary significantly between countries and infections treated-from five to 10 days of treatment.Conclusion In the capacity of a well-established network for antibiotic stewardship, we have enlightened the differences in Scandinavian ARTI antibiotic treatment recommendations. This paper is the first step moving forward to scrutinizing the potential for harmonizing recommendations for Denmark, Norway and Sweden-to help ensure continued supply of phenoxymethylpenicillin for use within the Scandinavian countries.